Analisis Pengaruh Pemeliharaan Preventif Jaringan Distribusi 20kV Pada Penyulang Gu.03 Terhadap Indeks Keandalan Jaringan di PT.PLN (Persero) ULP Medan Timur - Fitria Anis; Dicky Lesmana; Parlin Siagian (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The large number of disturbances that occur at the feeders result in power outages, which have an impact on reducing the reliability of the electricity system. One of the faults that occurred in the PT. PLN (Persero) ULP Medan Timur is a broken cable/wire cross section on a medium voltage overhead line (SUTM) or a damaged component of a medium voltage overhead line (SUTM). As a result, the energy (kWh) produced by the generator cannot be distributed, resulting in significant losses for PLN and losses for consumers. Therefore, the step taken to prevent this failure is to carry out preventive maintenance on the feeder. From the results of preventive maintenance obtained in this research, it was found that SAIDI = 0.1057 hours/customer/year, SAIFI = 0.0528 times/customer/year, CAIDI = 2.001 hours/time CAIFI = 0. 4995 hrs/hour, ASAI = 0.9997, ASUI = 0.0002, while from the results of corrective maintenance it was found that SAIDI = 0.4414 hrs/customer/year, SAIFI = 0.2643 hrs/customer/year, CAIDI = 1.67 hrs/time. CAIFI = 0.5987 times/hour, ASAI = 0.9990, ASUI = 0.0009. Thus, comparing the results of the calculation of the overall reliability value on the GU.03 feeder after preventive maintenance in 2022 in PT. PLN (Persero) ULP Medan Timur work area SAIDI = 0.0211 hours/customer/year, SAIFI = 0.2643 times/customer/year, CAIDI = 0.7983 hours/time, CAIFI = 12.526 times/hour, ASAI = 0.99995, ASUI = 0.00004.